(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: This scoping review aims to synthesize the use and perceptions of pod-based electronic cigarettes worldwide. Methods: We conducted a search in PubMed, Embase, and Web of Science in July 2024. The search strategy included keywords related to "pod-based electronic cigarettes," "use," and "perception." We selected observational studies reporting the prevalence of pod-based electronic cigarette usage and perceptions regarding pod-based electronic cigarettes. Results: From 2,269 articles found in the databases, we selected 14 articles for our final review, including 12 studies focusing on the prevalence of pod-based electronic cigarette usage and seven studies examining perceptions related to these devices. The prevalence of ever using pod-based electronic cigarettes varied significantly, ranging from 5.9% to 29.2%. In contrast, the current usage rate was lower, falling between 1.6% and 23.2%. Additionally, the perception of the harms associated with pod-based electronic cigarettes encompassed a wide range, with figures between 53.8% and 91.3%. Meanwhile, the perception of their addictiveness varied from 32.7% to 91.5%. Conclusion: The prevalence of pod-based electronic cigarette use was relatively high, with youth showing a greater tendency to use pod-style electronic cigarettes compared to young adults. Additionally, studies focusing on electronic cigarette users revealed lower perceptions of the harmful effects and the addictiveness of pod-based electronic cigarettes compared to studies conducted on the general population.